2014
DOI: 10.1016/j.jtcvs.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the underlying heart disease affects survival in pediatric patients undergoing extracorporeal cardiopulmonary resuscitation

Abstract: ECPR was associated with modest survival in pediatric patients with heart disease; however, this was associated in part with the underlying disease and pre-existing comorbidities, including the presence of acute kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
2
23
0
1
Order By: Relevance
“…The primary finding of our study is that our cohort of patients had an overall survival to hospital discharge of 43.8%, with 75% of these patients having either normal neurologic function or only mild disability. Our reported survival is comparable to previous paediatric cardiac extracorporeal cardiopulmonary resuscitation studies that reported a survival of 20-46%, 2,11,12,[18][19][20][21][22][23][24] but differs from other studies with more favourable extracorporeal cardiopulmonary resuscitation survival rates of 51-79%. Many prior studies of extracorporeal cardiopulmonary resuscitation include patients with wide ranges of duration of chest compressions prior to cannulation, some of them including patients receiving less than 10 minutes of cardiopulmonary resuscitation prior to placement on mechanical support.…”
Section: Discussionsupporting
confidence: 77%
“…The primary finding of our study is that our cohort of patients had an overall survival to hospital discharge of 43.8%, with 75% of these patients having either normal neurologic function or only mild disability. Our reported survival is comparable to previous paediatric cardiac extracorporeal cardiopulmonary resuscitation studies that reported a survival of 20-46%, 2,11,12,[18][19][20][21][22][23][24] but differs from other studies with more favourable extracorporeal cardiopulmonary resuscitation survival rates of 51-79%. Many prior studies of extracorporeal cardiopulmonary resuscitation include patients with wide ranges of duration of chest compressions prior to cannulation, some of them including patients receiving less than 10 minutes of cardiopulmonary resuscitation prior to placement on mechanical support.…”
Section: Discussionsupporting
confidence: 77%
“…Current evidence in the pediatric literature describing the frequency of ECMO cannulation site and its impact on outcomes remains limited to a small number of retrospective single-center studies and ELSO registry analyses. These studies present conflicting conclusions regarding the impact of carotid versus femoral and/or central cannulation on mortality and CNS injury (6, 8, 9, 18, 35, 36). Furthermore, results in these investigations often describe a wide variety of patients undergoing veno-arterial (VA) ECMO (cardiac, respiratory, or E-CPR) further limiting our ability to distinguish associations with mortality and/or neurologic outcomes specifically within the E-CPR population (3739).…”
Section: Discussionmentioning
confidence: 99%
“…Effective and efficient E-CPR requires a complex interplay of care made up of dedicated personnel, equipment, and clinical expertise. Although E-CPR has evolved from its origins in the management of pediatric postcardiotomy cardiac arrest patients to include noncardiac and adult patient populations (17), it remains commonly used by patients with congenital and acquired heart disease (818). Many retrospective reports of E-CPR use in the pediatric cardiac population have investigated risk factors for mortality and neurologic outcome; yet, our understanding of the inter- and intrainstitutional variability in the process of E-CPR is lacking.…”
mentioning
confidence: 99%
“…The published rates of survival to hospital discharge have varied widely. For cardiac ECMO‐cardiopulmonary resuscitation (eCPR), survival has been reported at 46% . For single ventricle patients, the overall survival rate has been reported at 37%, but for Glenn, Fontan, and total anomalous pulmonary venous connection patients, the survival rate is much lower yet .…”
Section: Discussionmentioning
confidence: 99%